Insights Into GLP-1 and GIP Actions Emerging From Vildagliptin Mechanism Studies in Man - Foley, James E. (Frontiers in Endocrinology, 2019)
Vildagliptin blocks glucagon like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) inactivation of the meal induced increases in GLP-1 and GIP so that elevated GLP-1 and GIP levels are maintained over 24 h. The primary insulin secretion effect of vildagliptin is to improve the impaired sensitivity of the β-cells to glucose in subjects with impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) and in patients with type 2 diabetes mellitus (T2DM); this effect was seen acutely and maintained over at least 2 years in patients with T2DM. Vildagliptin was also associated with improved β-cell function that is likely secondary to the improved metabolic state. Although there was no evidence of restoration of β-cell mass, the preponderance of the vildagliptin data does indicate that for at least 2 years β-cell function was maintained in vildagliptin treated patients but not in the untreated patients. Vildagliptin suppressed an inappropriate glucagon response to an oral glucose challenge in patients with T2DM, to a mixed meal challenge in patients with T2DM and type 1 diabetes mellitus, and to a mixed meal challenge in subjects with IGT and IFG. The improved glucagon response was maintained for at least 2 years in patients with T2DM and there was no change in the glucagon response in normoglycemic individuals. Vildagliptin lowered glucose levels into the normal range without increasing hypoglycemia. These hypoglycemic benefits appear to be secondary in large part to the improved sensitivity of both the β and α-cell to glucose. In the case of the α-cell, if glucose levels are high, GLP-1 attenuates the glucagon levels and if glucose levels are low, GIP increases glucagon levels. Vildagliptin reduces fatty acid flux from the adipocyte leading to reduced liver fat which in turn leads to increased glucose utilization. The reduced glycosuria and reduced lipo-toxicity associated with vildagliptin therapy does not lead to weight gain presumably due to increased fat mobilization and oxidation during meals and to reduced fat extraction from the gut.